2019
DOI: 10.1097/qai.0000000000001895
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Rate of Nicotine Metabolism and Tobacco Use Among Persons With HIV: Implications for Treatment and Research

Abstract: Background:The nicotine metabolite ratio (NMR) is a biomarker that represents individual variation in the speed that nicotine is metabolized. The rate of nicotine metabolism alters smoking behavior (e.g., amount) and has been validated for personalizing tobacco dependence medication selection to increase treatment efficacy and reduce treatment side effects in the general population of smokers. While smoking rates are extremely high among those with HIV, the NMR has not been evaluated in this underserved popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
3
12
3
Order By: Relevance
“…Ashare et al found that the mean NMR levels in PWH was 0.47, compared with 0.34 in PWOH; Schnoll et al found that PWH not on efavirenzcontaining ART had an NMR of 0.44. 12,13 Our finding of similar NMR before and after HIV seroconversion-at levels consistent with other studies of PWH-may suggest that a higher NMR reported in other studies of PWH reflects a higher baseline CYP2A6 activity in persons who acquire HIV, rather than a direct effect of HIV infection itself. These findings may suggest that higher CYP2A6 activity may be in the causal pathway for HIV acquisition, while ART may further increase the NMR.…”
Section: Discussionsupporting
confidence: 89%
“…Ashare et al found that the mean NMR levels in PWH was 0.47, compared with 0.34 in PWOH; Schnoll et al found that PWH not on efavirenzcontaining ART had an NMR of 0.44. 12,13 Our finding of similar NMR before and after HIV seroconversion-at levels consistent with other studies of PWH-may suggest that a higher NMR reported in other studies of PWH reflects a higher baseline CYP2A6 activity in persons who acquire HIV, rather than a direct effect of HIV infection itself. These findings may suggest that higher CYP2A6 activity may be in the causal pathway for HIV acquisition, while ART may further increase the NMR.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that among ever smokers about a 25% of PLWH and more than half the general population had stopped smoking at the time of data collection. This low quitting rate among PLWH may be related to many factors, such as a high level of nicotine dependence and/or with a faster nicotine metabolism observed in PLWH [24]. In our study, we could not directly compare the degree of nicotine dependence between PLWH and the general population, because this information was not collected in the ISTAT survey.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, use of the antiretroviral drug efavirenz, a CYP2A6 substrate, has been associated with greater NMR. 15 We investigated whether viral suppression on effective ART resulted in increased NMR compared with periods of uncontrolled viremia off-ART in a cohort of smokers with HIV. In addition, we hypothesized that efavirenz-containing regimens would be associated with the greatest increases in NMR compared with other ART regimens.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, use of the antiretroviral drug efavirenz, a CYP2A6 substrate, has been associated with greater NMR. 15…”
Section: Introductionmentioning
confidence: 99%